PENGARUH BUDAYA KERJA DAN ETOS KERJA TERHADAP KINERJA KARYAWAN PT DHARMA POLIMETAL Tbk - Ririn Uke Saraswati; Soedjatmoko; Sanjaya, Bagas (Universitas Bina Taruna Gorontalo, 2025)
The study aims to analyze the influence of work culture and work ethic on employee performance. Several causes affect employee performance, such as performance culture and work ethic. The high number of employee resignations in the Fastener department of PT Dharma Polimetal Tbk indicates a problem in performance. The study was conducted using a quantitative method. The population was 120 employees of the fastener department. With the Slovin formula, a sample of 93 was obtained. Data collection using a questionnaire. The sampling technique used the purposive sampling method, Data selection was carried out through validity tests, reliability tests, normality tests, Data analysis was carried out using multiple linear regression analysis methods, T tests, F tests and determination coefficients through the SPSS Version 26 application. The results of the study illustrate that the variables of work culture and work ethic have a positive and significant effect on employee performance both partially and simultaneously. The output of the determination test illustrates the influence of work culture and work ethic on performance by 40%. The existence of a study can be understood that the better the work culture implemented by the company and the better the employee work ethic, the higher the level of employee performance in business.